ECG Predictors for New-Onset Atrial Fibrillation Within a Year After Radiofrequency Ablation of Counterclockwise-Rotating Atrial Flutter - Liu, Hailei; Gu, Zhoushan; Zhu, Chao; Li, Mingfang; Jiao, Jincheng; Chen, Hongwu; Yang, Gang; Ju, Weizhu; Gu, Kai; Zhang, Fengxiang; Chen, Lin Yee; Yang, Di; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background - New-onset atrial fibrillation (AF) after ablation of typical atrial flutter (AFL) is not rare. This study aimed to investigate predictive value of electrocardiographic parameters on new-onset AF post typical AFL ablation. Methods - 158 consecutive patients (79.1% male, mean age 57.8±14.3 years) with typical AFL were enrolled between January 2012 and August 2017 in this single-center study. Patients with a history of AF before ablation were excluded. ECGs during sinus rhythm (SR) and AFL were collected. The duration of the negative component of flutter wave in lead II (DFNII), proportion of the DFNII of the total circle length of AFL (DFNII%), amplitude of the negative component of flutter wave in lead II (AFNII), duration (DPNV1) and amplitude (APNV1) of negative component of the P wave in lead V1, and P wave duration in lead II (DPII) during sinus rhythm were measured. Results - During a medium follow-up of 26.9±11.8 months, 22 cases (13.9%) developed new-onset AF. DFNII was significantly longer in patients with new-onset AF compared to patients without AF (114.7±29.6ms vs. 82.7±12.8ms, p<0.0001). AFNII was significantly lower (0.118±0.034mv vs. 0.168±0.051mv, p<0.0001), DPII (144.21±23.77ms vs. 111.46±14.19ms, p<0.0001) and DPNV1 was significantly longer (81.07±16.87ms vs. 59.86±14.42ms, p<0.0001) in patients with new-onset AF. No significant difference was found between the two groups regarding APNV1 (0.086±0.022mv vs. 0.103±0.034mv, P=0.077). Conclusions - Parameters representing left atrial activation from both P wave and flutter wave were valuable in predicting new-onset AF after AFL ablation. The parameters obtained during AFL might have some advantages over those during SR. Duration-related parameters, DFNII were independent risk predictors of new-onset AF.